Smallholder Cocoa Farmers Access to On/Off-Farm Support Services and its Contribution to Output in the Eastern Region of Ghana - Onumah, Justina A; Williams, Portia Adade; Quaye , Wilhelmina; Akuffobea, Mavis; Akuffobea, Mavis (Asian Journal of Agriculture and Rural Development, 2014)
It has been established that smallholder farmers have minimal access to various support services that would have otherwise enabled them to increase their output levels. The focus of this paper is to identify and quantify the impact of various support services on the production levels of cocoa in the Eastern region of Ghana. A cross sectional survey of 190 cocoa farmers was obtained using a two-stage sampling technique (purposive and random). Descriptive statistics and an OLS regression model were used to analyse and discuss the results of the study. The various support services identified included labour services, financial services, technical assistance, farmer group support services, Research and Development (R&D) institutional support services, extension services and input support services. The services that significantly influenced output levels of cocoa were extension services, labour supply and technical assistance, among other variables including farm size and quantity of agrochemical used. It is recommended that access to these support services be improved in order to realise an increase in output for the smallholder cocoa farmer.